2020
DOI: 10.1016/j.eclinm.2020.100455
|View full text |Cite
|
Sign up to set email alerts
|

The association of race and COVID-19 mortality

Abstract: Background COVID-19 mortality disproportionately affects the Black population in the United States (US). To explore this association a cohort study was undertaken. Methods We assembled a cohort of 505,992 patients receiving ambulatory care at Bronx Montefiore Health System (BMHS) between 1/1/18 and 1/1/20 to evaluate the relative risk of hospitalization and death in two time-periods, the pre-COVID time-period (1/1/20–2/15/20) and COVID time-period (3/1/20–4/15/20). COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
194
7
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 17 publications
12
194
7
12
Order By: Relevance
“…The significant associations of minority races/ethnicities with SARS-CoV-2 infection and COVID-19-related hospitalization builds on previous analyses of Black and Hispanic patients (24)(25)(26)(27). However, unlike previous studies, we found a significant association between Hispanic race/ethnicity and hospital mortality among older patients.…”
Section: Discussionsupporting
confidence: 74%
“…The significant associations of minority races/ethnicities with SARS-CoV-2 infection and COVID-19-related hospitalization builds on previous analyses of Black and Hispanic patients (24)(25)(26)(27). However, unlike previous studies, we found a significant association between Hispanic race/ethnicity and hospital mortality among older patients.…”
Section: Discussionsupporting
confidence: 74%
“…This finding is similar to outcomes identified in other NYC boroughs. Golestaneh et al found that Blacks and Hispanics with COVID-19 were more likely than Whites with COVID-19 to require hospitalization, but in-hospital mortality was equivalent across all three groups [19]. The authors also observed that both Hispanics and Blacks were more likely to test positive for SARS-CoV-2 than Whites, even when adjusting for medical comorbidities and sociodemographic factors, thereby hinting at a greater risk for SARS-CoV-2 exposure among these minority groups compared with Whites.…”
Section: Discussionmentioning
confidence: 99%
“…The novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has tested the infrastructure of health systems worldwide. At the writing of this article, over 5 million people nationwide have been confirmed to be infected with coronavirus disease-2019 (COVID- 19), the illness caused by SARS-CoV-2 [1]. The mortality rate for COVID-19 remains more than 10 times higher than that of influenza despite the lower prevalence rate [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that our results and analyzes on the race/color factor should be considered incipient and encourage further studies 19,20 . The analysis of COVID-19 mortality among race/color groups is more complex, as this population division is more subjective and performed differently in different situations.…”
Section: Discussionmentioning
confidence: 73%